Completing the EU Customs Union. The Effects of Trade Procedure Harmonization - Maria Persson; Yves Bourdet (Research Institute of Industrial Economics (IFN), 2010)
A main component of customs unions is a common trade policy on imports from non-member countries. Trade policy covers both tariff and non-tariff barriers like trade procedures. We argue that since trade procedures vary markedly across EU countries, the EU is not, strictly speaking, a customs union. To illustrate this, we estimate the impact of trade procedures on exports from non-EU countries and find a highly statistically significant and negative effect. Simulating what the effects would be of harmonizing trade procedures, i.e. to actually complete the EU customs union, we find that aggregated exports to the EU would increase by 20 percent for the average exporter.
Keywords: C23; F15; O24; 330; Customs Union; Economic Integration; European Union; Time Delays; Trade Facilitation; Trade Procedures; Zollunion; Außenhandelspolitik; Handelshemmnisse; Panel; EU-Staaten